Plant-derived Exosomes: Pioneering Breakthroughs in Therapeutics, Targeted Drug Delivery, and Regenerative Medicine - Dutta, Srabona; Ghosh, Sourav; Rahaman, Monosiz; Chowdhary, Sejuti Ray (Pharmaceutical Nanotechnology, 2025)
Small extracellular vesicles called exosomes, which cells release, have drawn a lot of attention recently because of their ability to serve as therapeutic delivery systems for drugs and regenerative medicine applications. The investigation of plant-based exosomes as a cutting-edge platform for drug administration has emerged as an enticing research topic. A summary of the pharmaceutical feasibility of exosomes generated from plants and their uses in drug delivery along with regenerative medicine are the goals of this review study. Plant exosomes can be combined into nanoparticle-based medication delivery systems to increase their stability, targeting, and cargo delivery capabilities. By loading plant exosomes with therapeutic compounds and encapsulating them within nanoparticles, controlled release and targeted distribution to specific cells or tissues may be achieved. In gene therapy, plant exosomes can be modified to carry nucleic acids like plasmid DNA, siRNA, or miRNA. Effective gene delivery and therapeutic gene expression regulation can be accomplished by encasing nucleic acids in exosomes or surface-modifying exosomes to improve their interaction with target cells. In this review, we through the history and features of plant exosomes, examine how they differ from mammalian exosomes, and consider how they may be used for gene therapy, tissue regeneration, and targeted medication delivery. The difficulties and prospects for creating exosome-based plant medicines are also explored.
Keywords: Plant exosome